2021 IEEE/ACM 29th International Conference on Program Comprehension (ICPC) 2021
DOI: 10.1109/icpc52881.2021.00030
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Community Smells’ Occurrence on Individual Developers by Sentiments

Abstract: Community smells appear in sub-optimal software development community structures, causing unforeseen additional project costs, e.g., lower productivity and more technical debt. Previous studies analyzed and predicted community smells in the granularity of community sub-groups using socio-technical factors. However, refactoring such smells requires the effort of developers individually. To eliminate them, supportive measures for every developer should be constructed according to their motifs and working states.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…We categorized 24 studies as empirical and one as theoretical according to Appendix A. Empirical studies conducted by Tamburri [5,11,20,42] and Palomba [10] offer information about the identification of the causes and effects of community smells in practice, information about the impact on work settings, and management approaches. The remaining included studies provide further information on community smells in relationship with development communities and processes [14,32,33,34,43,44,45,46] and research contributions such as models [12,13,16,47,48,49,50,51,52,53], organizational strategies [15], and tools [54]. We organized our results around the research questions described in Section 3.…”
Section: Reporting the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We categorized 24 studies as empirical and one as theoretical according to Appendix A. Empirical studies conducted by Tamburri [5,11,20,42] and Palomba [10] offer information about the identification of the causes and effects of community smells in practice, information about the impact on work settings, and management approaches. The remaining included studies provide further information on community smells in relationship with development communities and processes [14,32,33,34,43,44,45,46] and research contributions such as models [12,13,16,47,48,49,50,51,52,53], organizational strategies [15], and tools [54]. We organized our results around the research questions described in Section 3.…”
Section: Reporting the Resultsmentioning
confidence: 99%
“…Huang et al developed and enhanced the performance of a prediction model that detects community smells based on sentiment analysis in three scenarios, i.e., cross-project, within-project, and time-wise validation [51,52]. The study included ten process metrics to capture developers' activities.…”
Section: Statistical Modelsmentioning
confidence: 99%
“…The trend of some features is still unclear in Table 15, and the difficulty to interpret sentiments in line with other socio-technical research, indicating sentiment-related problems are multifaceted. 15,38,39,91 A notable example is the distribution of R_SEN_VAL. A related study 39 indicated that contributors are in higher productivity dealing with challenging and important tasks.…”
Section: Resultsmentioning
confidence: 99%
“…42 Tamburri et al 42 implemented a community smell detection tool called CODEFACE4SMELLS which evaluates development mailing list and software repository history information to detect various community smells. Based on their study, we 15 improved the prediction of community smell occurrence on individual developers by involving their sentiments, and we also suggested that developers should communicate in a straightforward and polite way to improve community healthiness. Driven by the suggestion of the empirical study on practitioners, 8 we intend to involve more aspects related to developers and third-party systems, and thus, the prior sociotechnical analysis outcomes can provide evidence on how to model contributors' characteristics in terms of their sentiments and OSS activities.…”
Section: Socio-technical Analysis On Developersmentioning
confidence: 99%
“…Using the computational tool "CODEFACE4SMELLS", [Huang et al 2021] labeled "state of the art" and used the tool to detect some community smells using email list and information about the history of a software repository. The authors suggested a technique based on developer sentiment analysis to predict the occurrence of some community smells.…”
Section: Related Workmentioning
confidence: 99%